BUSINESS PROCESS EVALUATION OF PROCUREMENT OF GOODS AND SERVICES BY IMPLEMENTING ORACLE AT UPT PROCUREMENT OF ITB USING THE MONTE CARLO SIMULATION METHOD - Gede Agus Giri Astama Putra, I
ITB Procurement Unit plans to transform its business process by implementing Oracle as the main procurement information system to replace SIMAJIK. It will take a long time and cost a lot of money. Therefore, it is important to prepare all aspects well before implementing the Oracle business process design that has been made. This research aims to evaluate the ITB Procurement Unit's design The initial stage is to map the existing business processes and Oracle with Cross Functional Diagram, then followed by gathering simulation parameters. After that, the simulation is conducted using the Monte Carlo Simulation method to calculate time performance, and the last step is to compare the results between business processes using the T-Test and F-Test. After performing the calculation, the average total time for the existing business process is 62.1 days in the combined method, 64.5 days in the tender method and 48.6 days in the framework contract method for the procurement of goods. For service procurement is 75.2 days in the combined method, 77.69 days in the tender method and 62.41 days in the framework contract method. As for the Oracle business process is 46.7 days for the combined method, 47.37 days for the tender method and 41.84 days for the framework contract method, and for the Oracle business process by implementing inventory is 43.04 days in the framework contract method. After comparing the results using T-test and F-test, it is found that the Oracle business process is significantly better in time performance compared to the existing business process.